Estimation in Linear Regression Models with Disparate Data Points - Krasker, William S. (Econometrica, 1980)
[This paper addresses the problem of estimating unknown regression coefficients when erroneous data and other violations of the standard assumptions are possible. An estimator which has a limited sensitivity to these departures from the assumptions is presented, and some of its properties are derived. This estimator is shown to have a certain efficiency property relative to other estimators with the same sensitivity to erroneous data.]